The scope, content and normative value of the presumption of innocence in the South African law of criminal procedure and evidence - Schwikkard, Pamela-Jane (Stellenbosch : Stellenbosch University, 2012)
Thesis (LL.D) -- University of Stellenbosch, 1999.